Ղազարոս Սարյան -«Սիմֆոնիկ պոեմ» - Արմենի Հյուսնունց, Շուշան (Musical Armenia, 2010)
Analytical article of a musicologist, graduate student of the Yerevan State Conservatory after Komitas, Shushan Armen Husnunts “Symphonic Poem of Lazar Saryan” about the creation of a one-part tone poem as a research paper and the first symphonic canvase in 1950. In the theoretical aspect the paper completely covers all the advantages of the composition.